Enzalutamide inhibits testosterone-induced growth of human prostate cancer xenografts in zebrafish and can induce bradycardia. Issue 1 (December 2017) - Melong, Nicole; Steele, Shelby; MacDonald, Morgan; Holly, Alice; Collins, Colin; Zoubeidi, Amina; Berman, Jason; Dellaire, Graham
Abstract The zebrafish has become a popular human tumour xenograft model, particularly for solid tumours including prostate cancer (PCa). To date PCa xenotransplantation studies in zebrafish have not been performed in the presence of testosterone, even when employing androgen-dependent cell models, such as the LNCaP cell line. Thus, with the goal of more faithfully modelling the hormonal milieu in which PCa develops in humans, we sought to determine the effects of exogenous testosterone on the growth of LNCaP, or androgen-independent C4-2 cells xenografted into zebrafish embryos. Testosterone significantly increased engrafted LNCaP proliferation compared to control xenografts, which could be inhibited by co-administration of the anti-androgen receptor drug, enzalutamide. By contrast, C4-2 cell growth was not affected by either testosterone or enzalutamide. Enzalutamide also induced bradycardia and death in zebrafish embryos in a dose-dependent manner and strongly synergized with the potassium-channel blocking agent, terfenadine, known to induce long QT syndrome and cardiac arrhythmia. Together, these data not only indicate that testosterone administration should be considered in all PCa xenograft studies in zebrafish but also highlights the unique opportunity of this preclinical platform to simultaneously evaluate efficacy and toxicity of novel therapies and/or protective agents towards developing safer and more effective PCa treatments.